KONSEP DAKWAH DALAM PENGEMBANGAN MASYARAKAT ISLAM - Nasrl Nasril (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
Social history of Muslims is born , grows and develops could not be separated with a history of the rise and fall of social processes Muslims in preaching , theologically considered proselytizing (mission Sacre ) rewarding project and position of propaganda itself is a conditio sine quanon presence , and inherently not be prevented . About this fact should be recognized correctly that the Prophet Muhammad said in his message "Say what you have received from me even one verse " therefore reasonable in stage history working approach propaganda continue to be born both technical and operational or conceptual course can not be removed with the social context , specific reality